Determinants of Indonesia’s Residence Traveling Abroad - Akhmad Tantowi (JIET (Jurnal Ilmu Ekonomi Terapan), 2021)
The study aims to identify the economic variables affecting Indonesia’s residence to travel abroad. Knowledge of the variables of Indonesia’s residence to travel abroad is very important because this is one of the sources of foreign exchange leakage. The ARDL approach will be used with time series data for the period 1992-2019. The impact of changes in income, relative prices for Malaysian tourism, and flight availability will be estimated and tested. Two dummy variables are also provided to represent the economic crisis in 1997-1998 and the global financial crisis in 2008. One of the important findings of this study is the significance of the income variable with more than one elasticity, which shows the luxury nature of tourism travel. The relative price of tourism also affects Indonesians to travel abroad in the long- and short-run. The economic crisis of 1997-1998 led to a decrease in Indonesians traveling abroad.